The Taliban: From Past to Present and the Question of Whether It Can be Recognized as Government Under International Law - Nuray Ekşi (Public and Private International Law Bulletin)
In international law, there is a difference between the recognition of states and governments. Governments established under a state’s constitution do not need to be recognized by other states. However, governments that came to power in an unconstitutional and illegal process would have to be recognized by other states. Although Afghanistan remains a state, it faces the question of whether the entities that took over the administration in violation of the Afghan constitution can be recognized as a legitimate government by other states. Only Pakistan, the United Arab Emirates, and Saudi Arabia recognized the Taliban who seized power illegally between 1996 and 2001, as an established government. After the United States intervened and launched an operation in Afghanistan, blaming Taliban for being a sanctuary for Osama bin Laden and al-Qaeda members who allegedly perpetrated the twin-tower attack, the Taliban gave up the administration and fled to the mountains. Despite the continued presence of the United States and its allies in Afghanistan for almost two decades, the Taliban grew stronger. The Agreement for Bringing Peace to Afghanistan between the Islamic Emirate of Afghanistan, another name for Taliban, was signed in Doha on February 29, 2020, with the United States of America. After the bilateral agreement, on November 17, 2020, the United States announced that it would withdraw its troops from Afghanistan. Hence, President Joe Biden of the United States announced the country’s decision to withdraw from Afghanistan completely on April 14, 2020. The Government of the Islamic Republic of Afghanistan was conquered on August 15, 2021, after the Taliban seized Kabul without conflict. With the fall of the Government of the Islamic Republic of Afghanistan, the Taliban gained de facto control of the country. In this study, information will be given about the Taliban from past to present. Then, the types of recognition and the differences between the recognition of states and the recognition of governments in terms of international law will be explained. Lastly, the issue of whether the Taliban can be recognized as a government will be examined.